Step
*
1
of Lemma
sine-rminus
1. x : ℝ
2. Σi.-1^i * (x^(2 * i) + 1)/((2 * i) + 1)! = sine(x)
3. Σi.-1^i * (-(x^(2 * i) + 1))/((2 * i) + 1)! = sine(-(x))
4. ∀i:ℕ. isOdd((2 * i) + 1) = tt
5. ∀[a,b:ℝ].
     (a = b) supposing 
        (Σn.-1^n * (-(x^(2 * n) + 1))/((2 * n) + 1)! = b and 
        Σn.-1^n * (-(x^(2 * n) + 1))/((2 * n) + 1)! = a)
⊢ Σn.-1^n * (-(x^(2 * n) + 1))/((2 * n) + 1)! = -(sine(x))
BY
{ ((InstLemma `series-sum-linear2` [⌜λ2i.-1^i * (x^(2 * i) + 1)/((2 * i) + 1)!⌝;⌜sine(x)⌝;⌜r(-1)⌝]⋅ THENA Auto)
   THEN MoveToConcl (-1)
   THEN BLemma `series-sum_functionality`
   THEN Auto) }
1
1. x : ℝ
2. Σi.-1^i * (x^(2 * i) + 1)/((2 * i) + 1)! = sine(x)
3. Σi.-1^i * (-(x^(2 * i) + 1))/((2 * i) + 1)! = sine(-(x))
4. ∀i:ℕ. isOdd((2 * i) + 1) = tt
5. ∀[a,b:ℝ].
     (a = b) supposing 
        (Σn.-1^n * (-(x^(2 * n) + 1))/((2 * n) + 1)! = b and 
        Σn.-1^n * (-(x^(2 * n) + 1))/((2 * n) + 1)! = a)
6. n : ℕ
⊢ (r(-1) * -1^n * (x^(2 * n) + 1)/((2 * n) + 1)!) = -1^n * (-(x^(2 * n) + 1))/((2 * n) + 1)!
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  \mSigma{}i.-1\^{}i  *  (x\^{}(2  *  i)  +  1)/((2  *  i)  +  1)!  =  sine(x)
3.  \mSigma{}i.-1\^{}i  *  (-(x\^{}(2  *  i)  +  1))/((2  *  i)  +  1)!  =  sine(-(x))
4.  \mforall{}i:\mBbbN{}.  isOdd((2  *  i)  +  1)  =  tt
5.  \mforall{}[a,b:\mBbbR{}].
          (a  =  b)  supposing 
                (\mSigma{}n.-1\^{}n  *  (-(x\^{}(2  *  n)  +  1))/((2  *  n)  +  1)!  =  b  and 
                \mSigma{}n.-1\^{}n  *  (-(x\^{}(2  *  n)  +  1))/((2  *  n)  +  1)!  =  a)
\mvdash{}  \mSigma{}n.-1\^{}n  *  (-(x\^{}(2  *  n)  +  1))/((2  *  n)  +  1)!  =  -(sine(x))
By
Latex:
((InstLemma  `series-sum-linear2`  [\mkleeneopen{}\mlambda{}\msubtwo{}i.-1\^{}i  *  (x\^{}(2  *  i)  +  1)/((2  *  i)  +  1)!\mkleeneclose{};\mkleeneopen{}sine(x)\mkleeneclose{};\mkleeneopen{}r(-1)\mkleeneclose{}]\mcdot{}
    THENA  Auto
    )
  THEN  MoveToConcl  (-1)
  THEN  BLemma  `series-sum\_functionality`
  THEN  Auto)
Home
Index